The sharing economy and real estate market. The phenomenon of shared houses. - Sdino, Leopoldo; Magoni, Sara (Springer, 2018)
During the past decade, new forms of the sharing economy have been developed as an alternative tool for the satisfaction of heterogeneous needs. From both short- and long-distance transportation to the rental of apartments, this expanding economy has created a new private supply of those services that, traditionally, were only provided by professionals. In parallel with its unexpected development, the size of its impact on relatively traditional economic sectors has grown too. This fact has determined the need, an ever more one, for studies on the dynamics of this phenomenon. The short-term housing-rental sector plays a central role within the universe of the sharing economy. In fact, it has spawned a new rental market, parallel to the traditional one, that is characterized by short and very-short-term contracts and by the immediate and easily accessed encounter between demand and supply, made possible through the use of digital platforms. Airbnb plays, without any doubt, a leading role in this phenomenon. Born in the United States of America, it has had an astonishing global expansion in just a few years. In fact, currently, it operates in 191 countries, homogeneously, that is to say, without trying to match the enormous differences between local legislation on tourism and real estate to major procedural and systemic differences. This service was born in 2007, but it is only since 2013 that, in Italy, its presence has become massive; until then, only a few hundred listings were published for the whole nation. Its development has thus been exponential, and as the projections confirm, in all likelihood, in the next decade it will maintain the same rate of growth. By now, it has already been several years that researchers and operators have highlighted the influence of Airbnb in the market of tourist accommodations. What is still poorly detailed, perhaps because of its low visibility and immediacy, is the relationship that this kind of short-term rental contract has with the traditional real estate market. Therefore, the intent of this study is to take the first step towards the comprehension of the impact that the uncontrolled growth of the sharing economy has, specifically, on the Italian real estate market. Logically, the rental submarket is the one that is affected the most by the growth of the sharing economy. In fact, compared to traditional rentals, contracts that are stipulated with Airbnb provide lessors with much higher revenues and much lower restrictions. That is one of the reasons that the Airbnb's user base has experienced such an enormous expansion. However, this has also led to the fear that these new dynamics are liable to distort the traditional real estate market.
Keywords: Wohnungsvermietung; Wohnungswirtschaft; Unternehmensform; Zeitmietvertrag; Untervermietung; Mieterschutz; Tourismus; Internet; Sharing Economy